Criminalization of LGBT (Lesbian, Gay, Bisexual, and Transgender) Criminal Act and Its Law Enforcement Efforts in Indonesia - Ifahda Pratama Hapsari (Justitia Jurnal Hukum, 2021)
The law enforcement problems in many countries, especially in Indonesia, are central problems. The number of criminal cases is increasing in Indonesia, especially the increasing number of violence commit by LGBT people. Many factors influence LGBT crimes. A set of regulations is not enough to support the strict law enforcement officers. It also needs strict sanctions. In the Criminal Code concerning sanctions, the criminal act imposed on the perpetrators has been highlighted in Indonesia in terms of the process of seeking a sense of justice, which is a link that cannot be separated. It began when the laws and regulations were made, as well as the implementation and application. LGBT stands for Lesbian, Gay, Bisexual, and Transgender. It also refers to one’s sexual orientation, whether individuals are attracted to the same or different sexes/genders. LGBT mainly occur in big cities. It occurs due to lifestyle behaviors, a wrong circle of friends, or genetic factors inherited from birth. Trauma due to violence and the label of the wrong sexual orientation make their character dominant to commit violence. The Criminal Code in Indonesia, especially Article 292 of the Criminal Code, which has been used as a reference in giving sanctions to LGBT perpetrators, has not provided justice for the victims. This Article only contains limitations. Obscene acts are not enough to ensnare the perpetrators. The objective of this study was to ensure that LGBT perpetrators who commit violent crimes against victims can be punished according to criminal law in Indonesia.Keywords: Criminalization, LGBT, Law Enforcement.